Opioid Therapy and Sleep Disorders: Risks and Mitigation Strategies. Issue 1 (October 2015) - Cheatle, Martin D.; Webster, Lynn R.
Abstract Objective Patients with chronic pain frequently experience concomitant sleep disorders. There has been controversy on whether opioids have a beneficial or deleterious effect on sleep quality, duration and efficiency. There is also concern regarding the association between chronic opioid therapy (COT) and sleep disordered breathing (SDB) and the increased risk for unintentional opioid related overdose. This article provides a narrative review of the literature on the effect of opioids on sleep disorders and discusses risk assessment and mitigation strategies. Design A narrative review of the current literature on the effect of prescription opioids on sleep quality and efficiency, the relationship between opioids and sleep disorders and potential risk factors in patients with chronic pain. Results There is conflicting evidence regarding the benefit of opioids in improving sleep quality, duration and efficiency with several studies and reviews suggesting a beneficial effect of opioids on sleep and other studies demonstrating the opioids can cause sleep disturbance leading to hyperalgesia. There was credible evidence of a strong relationship between opioids and SDB with noted risk factors including use of methadone, high opioid dosing (>200 mg MED) and combining opioids with benzodiazepines. Conclusions Further research is required to elucidate the effect of prescription opioids on sleep quality and pain intensity and the risks associated with opioids and SDB. The risk of SDB should be routinely assessed in patients on COT.